Examining the Challenges of Early Childhood Education in Nigeria - Justina Chinyere Aguh; Adekunle Thomas Olutola (Indonesian Journal of Educational Research and Technology, 2023)
Early Childhood Education is an essential formal education given to children from conception to eight years for cognitive, social, and emotional development, language and speech development, and the development of fine and gross motor skills. Early childhood education reduces the rate of school dropout and higher school achievement and helps to curb the rate of juvenile arrests in society. However, early childhood education is faced with a lot of bottlenecks that intend to hinder the effectiveness of early childhood in Nigeria. These challenges comprise poor infrastructure facilities, poor numeration of teachers' salaries, inadequate implementation of early childhood curriculum, employment of unqualified and incompetent teachers with little or no in-depth knowledge of early childhood Developmental Appropriate Practices, corruption, and poor funding of early childhood programs, Proliferation of early childhood according to National Policy on Education is a pertinent issue that has led to a poor standard and lack of proper regulation of early childhood institutions across the country, the language of the immediate environment as a medium of instruction is not strictly adhered to most states in Nigeria among others. The study revealed that these challenges could be solved by adequately implementing, proper funding and supervision of early childhood programs in Nigeri.